Talent Management in The Digital Age: Leveraging Technology for HR Efficiency and Effectiveness - Cahyono, Nikotiyanto Dwi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
In the contemporary business environment, the digital transformation of talent management has become a critical factor for enhancing Human Resources (HR) efficiency and effectiveness. This study explores the integration of digital technologies within talent management practices and evaluates their impact on HR functions. By analyzing various case studies and conducting interviews with HR professionals, the research identifies key technological advancements such as AI-driven recruitment tools, data analytics platforms, and digital performance management systems. These technologies have streamlined HR processes, reduced administrative burdens, and improved decision-making accuracy. The findings reveal that digital tools facilitate the automation of routine tasks, enabling HR professionals to focus on strategic activities and thereby enhancing the quality of talent management practices. Additionally, the utilization of real-time data for employee performance, engagement, and development provides valuable insights that contribute to more informed decision-making and targeted interventions. However, the successful adoption of these technologies necessitates a well-defined strategy, including comprehensive training for HR personnel and alignment of technological solutions with organizational objectives. The study underscores the significance of leveraging technology to not only improve operational efficiency but also to elevate the overall effectiveness of HR functions. The results suggest that organizations can achieve a competitive advantage by incorporating digital solutions into their talent management strategies, ultimately driving organizational success. This research contributes to the understanding of how digital technologies can be strategically implemented to enhance HR practices and provides practical recommendations for organizations aiming to optimize their talent management processes in the digital age.